O óleo essencial de lippia microphylla cham. (verbenaceae) modula a via do Óxido nítrico para exercer efeito tocolítico em rata - Silva, Maria da Conceição Correia (2015)
Lippia microphylla Cham. (Verbenaceae), known as “alecrim-do-mato”, “alecrim-de-tabuleiro” and “alecrim-pimenta”, is populary used as antiseptic or to treat respiratory disorders. From its leaves, the essential oil (LM-OE) was extracted, that, according to Silva (2013), presented tocolytic effect on rat, with a probably indirect inhibition of Ca2+ influx through voltage-gated calcium channels (CaV). Thus, the aim of this work was to characterize the tocolytic action mechanism of LM-OE on rat. Isometric contractions were recorded to determine and compare the relative efficacy and potency (n = 5). Considering that the NO pathway can negatively modulate the CaV, we decided to evaluate this participation on rat uterus pre-contracted by oxytocin. For that, it was employed L-NAME, a non-selective inhibitor of NO synthase (NOS). The results show that the tocolytic potency of LM-OE (EC50 = 2.7 ± 0.6 μg/mL) was approximately 9.5-fold attenuated in the presence of L-NAME (EC50 = 25.6 ± 3.9 μg/mL). Furthermore, this reduction was reversed in the presence of the L-arginine (EC50 = 6.2 ± 1.7 μg/mL), a NOS substrate, and simultaneous presence of the L-arginine and L-NAME (EC50 = 7.2 ± 1.4 μg/mL), confirming the participation of NO pathway in the tocolytic action of LM-OE. Similarly, the relaxant potency of LM-OE was approximately 3.7-fold reduced in the presence of ODQ (EC50 = 10.1 ± 0.9 μg/mL), a soluble guanylate cyclase (sGC) inhibitor, and 3.3-fold in the presence of Rp-8-Br-PET-cGMPS (EC50 = 8.9 ± 0.9 μg/mL), a protein kinase G (PKG) inhibitor. Thus, LM-OE positively modulates the NO/sGC/PKG pathway to promote its tocolytic effect on rat. Given that this pathway can activate the K+ channels, it was questioned if these channels would be involved on tocolytic effect of LM-OE. To confirm this hypothesis, experiments were made in the presence of CsCl, a non-selective K+ channels blocker, and it was observed that the concentration-response curve of LM-OE (EC50 = 2.7 ± 0.6 μg/mL) was rightward shifted with an approximately 4.3-fold reduction on its relaxant potency, confirming the participation of K+ channels on tocolytic effect of essential oil. In order to verify the subtypes involved, it was employed selective blockers of K+ channels. Control concentration-response curve was also shifted to the right and the tocolytic potency of LM-OE was attenuated in the presence of tetraethylammonium (EC50 = 10.5 ± 0.3 μg/mL), apamin (EC50 = 10.0 ± 1.0 μg/mL), 4-aminopyridine (EC50 = 12.4 ± 2.0 μg/mL) and glibenclamide (EC50 = 9.7 ± 0.9 μg/mL), the large (BKCa) and small conductance (SKCa) calcium-activated, voltage-gated (KV) and adenosine triphosphate-sensitive (KATP) potassium channels blockers, respectively. Moreover, LM-OE had its tocolytic potency reduced in the same intensity when these four blockers were simultaneously incubated (EC50 = 16.6 ± 2.6 μg/mL), not observing synergistic effect. Therefore, the tocolytic action mechanism of LM-OE on rat involves the positive modulation of the NO/sGC/PKG/K+ channels pathway, suggesting the blockade of calcium influx through CaV, leading to the relaxation of uterine smooth muscle.